Social perception and social reality why accuracy dominates bias and self-fulfilling prophesy - Jussim, Lee J. (New York : Oxford University Press, 2012)
This title contests the received wisdom in the field of social psychology that suggests that social perception and judgment are generally flawed, biased, and powerfully self-fulfilling.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social perception; Stereotypes (Social psychology)